Ecological Sanitation, Sustainable Strategy as an Alternative Urban Water Source - Hin, Lai Sai; Mah, D.Y.S.; Putuhena, F.J.; Salim, Said (2008)
Water supply is one of the basic infrastructure requirements. Water treatment and supply are often granted a much higher priority than wastewater collection and treatment, despite the fact that wastewater deserves a greater emphasis due to the impact of its poor management has on public health. A new commitment to give wastewater the same priority as water supply is a very positive development. A pilot project of greywater ecological treatment is established in Kuching city since 2003. Such treatment facility opens up an opportunity of wastewater reclamation for reuse as secondary sources of water for non-consumptive purposes. This paper aims in exploring the potential of the intended purposes in the newly developed ecological treatment project. By utilizing the Wallingford Software model, InfoWorks WS (Water Supply) is employed to carry out a hydraulic modeling of a hypothetical greywater recycling system as an integrated part of the Kuching urban water supply, where the greywater is treated, recycled and reused in the domestic environment. The modeling efforts had shown water saving of more than 50% from the investigated system reinstating that the system presents an alternative water source worth-investing in an urban environment.